Resilient thinking : protecting organisations in the twenty-first century - Wood, Phillip (IT Governance Publishing Ltd, 2023)
Understand how organisations think, plan and deliver on the resilience 'mission' and how they should adapt when challenges arise. As the title suggests, Wood argues that all employees need to adopt 'resilient thinking' in order for their organisation to survive unprecedented circumstances.